2017
DOI: 10.1523/jneurosci.3353-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Truncated TrkB.T1-Mediated Astrocyte Dysfunction Contributes to Impaired Motor Function and Neuropathic Pain after Spinal Cord Injury

Abstract: Following spinal cord injury (SCI), astrocytes demonstrate long-lasting reactive changes, which are associated with the persistence of neuropathic pain and motor dysfunction. We previously demonstrated that upregulation of trkB.T1, a truncated isoform of the brainderived neurotrophic factor receptor (BDNF), contributes to gliosis after SCI, but little is known about the effects of trkB.T1 on the function of astrocytes. As trkB.T1 is the sole isoform of trkB receptors expressed on astrocytes, we examined the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 51 publications
8
79
0
Order By: Relevance
“…TrkB-T1 mediates BDNF-induced internalization of glycine transporters in astrocytes (Aroeira et al 2015) and modulates GABA transporters (Vaz et al 2011). A recent report describes that TrkB-T1 knockout mice-derived astrocytes exhibit decreased migration and proliferation in vitro (Matyas et al 2017). In line with these reports, our results suggest involvement of TrkB-T1 in BDNF protective effects, and show for the first time the protective role of astrocyte TrkB by mediating BDNF effects.…”
Section: Discussionsupporting
confidence: 89%
“…TrkB-T1 mediates BDNF-induced internalization of glycine transporters in astrocytes (Aroeira et al 2015) and modulates GABA transporters (Vaz et al 2011). A recent report describes that TrkB-T1 knockout mice-derived astrocytes exhibit decreased migration and proliferation in vitro (Matyas et al 2017). In line with these reports, our results suggest involvement of TrkB-T1 in BDNF protective effects, and show for the first time the protective role of astrocyte TrkB by mediating BDNF effects.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is further supported by a previous report that addition of recombinant BDNF to astrocyte monocultures increases cell area via TrkB.T1 mediated Rho GTPase activity (Ohira et al, 2005). In addition, following spinal cord injury, TrkB.T1 knockout astrocytes have slower migration/proliferation in response to BDNF and downregulated migration and proliferation pathways (Matyas et al, 2017). Interestingly, BDNF, TrkB, and astrocytic territory are all increased by exercise (Fahimi et al, 2017), which enhances cognition (Gomez-Pinilla and Hillman, 2013).…”
Section: Discussionsupporting
confidence: 76%
“…In a mouse model of Down syndrome, the accelerated death of hippocampal neurons is not rescued by exogenous BDNF delivery [12] but instead by restoring the physiological levels of TrkB.T1 [56]. In a mouse model of spinal cord injury, the increased levels of TrkB.T1 contribute to locomotor dysfunction and neuropathic pain [57]. In the present study, we showed that expression of TrkB-FL was significantly decreased after anesthesia and surgery, whereas TrkB-ICD was significantly increased.…”
Section: Discussionmentioning
confidence: 51%